Edukasi Dampak Pencemaran Lingkungan Pesisir Dan Pemberdayaan Masyarakat Pesisir Dalam Pengelolaan Sampah Melalui Pendekatan 3r (Reduce, Reuse Dan Recycle) Di Sekolah Dasar Integral Hidayatullah Tondo - Musayyadah Tis'in; Andi Heryanti Rukka; Nur Hasanah; Kasim Mansyur; Roni Hermawan; Aswad Ekaputra; Muh. Saleh Nurdin; Septina F. Mangitung; Samliok Ndobe; Rifki Fahrezi; Qur Ana (Jurnal Cendekia Mengabdi Berinovasi dan Berkarya, 2026)
Community service activities entitled “Education on the Impact of Coastal Environmental Pollution and Empowerment of Coastal Communities in Waste Management through the 3R Approach (Reduce, Reuse, and Recycle)” at Hidayatullah Integral Elementary School in Tondo Village, Palu City, aims to create a cleaner, healthier, and more sustainable coastal environment with high aesthetic value through the active involvement of the community in 3R-based waste management. This activity is beneficial in various aspects of community life, including environmental, social, economic, and educational aspects. The methods used to carry out this community service activity include education and socialization, training, and workshops. Additionally, this PKM activity series includes coastal clean-up actions as well as monitoring and evaluation aimed at assessing the program's effectiveness by observing changes in the awareness and behavior of the target audience in managing waste. The entire series of activities, including preparation, socialization, and counseling as well as beach clean-up actions, ran smoothly. Elementary school students, as the target audience, showed great enthusiasm for this activity.